2019
DOI: 10.4103/njs.njs_11_19
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of management of neonatal intestinal obstruction at a tertiary center in Nigeria

Abstract: Background:Intestinal obstruction in a newborn remains a significant emergency in pediatric surgery. Clinical presentation is often subtle with sudden deterioration of their clinical states. Clinical outcome in the developing countries is poor owing to a variety of factors.Objective:The objective of this study is to identify the factors affecting the management outcome in our environment.Patients and Methods:Data on clinical presentation, management, and outcome of all neonates managed for intestinal obstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 14 publications
4
40
1
1
Order By: Relevance
“…Reason for male sex predominance is not known, but it may be due to less attention towards female child by social custom in our society. Most common age group involved in our study was 1month to 1 year (34%) followed by neonatal age group (22%) [3,7,8]. Uba et al also studied and observed that 74% of patients were less than 1year [11].…”
Section: Discussionmentioning
confidence: 57%
“…Reason for male sex predominance is not known, but it may be due to less attention towards female child by social custom in our society. Most common age group involved in our study was 1month to 1 year (34%) followed by neonatal age group (22%) [3,7,8]. Uba et al also studied and observed that 74% of patients were less than 1year [11].…”
Section: Discussionmentioning
confidence: 57%
“… 20 In Nigeria, lithobezoar remains an uncommon cause of intestinal obstruction despite a high prevalence of IDA. 21 , 22 …”
Section: Introductionmentioning
confidence: 99%
“…Acute intestinal obstruction (AIO) in children is a common cause of paediatric surgical emergency. [ 1 2 3 4 ] Causes of AIO not only vary from neonatal period to older children but also based on geographical distribution. [ 3 5 6 ] In the advanced countries, the prognosis is improved by rapid diagnosis and quality of perioperative care.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 2 3 4 ] Causes of AIO not only vary from neonatal period to older children but also based on geographical distribution. [ 3 5 6 ] In the advanced countries, the prognosis is improved by rapid diagnosis and quality of perioperative care. [ 3 6 7 8 ] Contrariwise, in sub-Saharan Africa and other developing countries, delay in admission or management, lack of neonatal and paediatric intensive care, hard access to hospital and limited resources have been responsible for the poor prognosis of AIO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation